IMPLEMENTASI KEBIJAKAN PEMBANGUNAN PERUMAHAN BAGI MASYARAKAT BERPENGHASILAN RENDAH DI RUSUNAWA KELURAHAN DUSUN BESAR KECAMATAN SINGARAN PATI KOTA BENGKULU - Anita Marianata (UNIVED PRESS, Universitas Dehasen Bengkulu, 2014)
This study aims to determine the implementation of housing development policy for low income communities in Kelurahan Dusun Besar, Singaranpati Subdistrict, Bengkulu City. This study uses a qualitative desciptive method and the data collection was conducted through in-depth interviews, focus group discussions, and documentation method. The results shows that the implementation of Rusunawa (simple rented flats) policy development in Kelurahan Dusun Besar has not been appropriate with expectation. The physical condition of Rusunawa is not habitable, because the construction of Rusunawa has not finished or neglected until now. From the 96 residence in total, only 23 units were inhabited. The Rusunawa management also did not collect the rent, due the condition of facilities in Rusunawa was not adequate such as unavailable water supply. Besides, the Rusunawa management recognized that there was no authority resignation directly from the government of Bengkulu City to the management, so that the managers did not know exactly when these flats will be resolved or the rent expense will be charged. Moreover, there was no program to improve the economy of low-income communities, so the empowerment of low- income communities living in Rusunawa was impossible. Keywords: Implementation of Policy, Housing Policy, Socio-Economics, Low-Income Communities